Fantastyka i parafrazy. O dyskursie pamięci w twórczości pisarzy młodego pokolenia – Łukasz Orbitowski Widma (2012) i Paweł Demirski Niech żyje wojna! (2011) - Rutka, Anna (Tematy i Konteksty, 2015)
The present article discusses works by Łukasz Orbitowski and Paweł Demirski, two authors representing the young generation of Polish writers whose texts stand in the opposition to a worn-out and highly ritualised trend of national-symbolic interpretations of memory. The debunking literary strategy of both authors relies heavily on the aesthetics of subversion. Choosing for 'Spectres' the genre of historical fantasy, Łukasz Orbitowski provides himself with a vast space of artistic freedom, using it for free reinterpretations and continuations of the existing narratives of memory. The theatre of Paweł Demirski and Monika Strzępka, in turn, is a theatre of linguistic performance which clashes sequences of language that transmit historical imagination and national self-awareness of Poles. In Demirski’s play theatre becomes a medium of protest against fossilised forms of memory, where graphically staged painful trauma is deprived of the aura of sacrum. Triviality and vulgarism of language demolish both the elevated phrases of the national culture of memory and the naïve pop-cultural representations of war and the Warsaw Uprising.